2021
DOI: 10.3892/etm.2021.11092
|View full text |Cite
|
Sign up to set email alerts
|

PRUNE2 inhibits progression of colorectal cancer in vitro and in vivo

Abstract: Prune homolog 2 with BCH domain (PRUNE2) is associated with prostate cancer, neuroblastoma, glioblastoma and melanoma; however, the function of PRUNE2 in colorectal cancer (CRC) remains unknown. The present study aimed to evaluate the effects of PRUNE2 on the development of CRC. The biological function of PRUNE2 in CRC cell lines was investigated by using Cell Counting Kit-8, colony formation, flow cytometry and Transwell assay. Additionally, a mouse model was established to investigate the effect of PRUNE2 on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
(45 reference statements)
0
3
0
Order By: Relevance
“…Interestingly, we previously demonstrated that PRUNE2 has the same functions as FOXF2 in CRC, and the survival prognosis of patients with low expression of PRUNE2 was poor. 42 Thus, we speculated that FOXF2 may regulate PRUNE2 and that this regulatory correlation may play an important role in CRC. Herein, we identified PRUNE2 as a novel transcriptional target of FOXF2 and demonstrated that FOXF2 regulated the proliferation and progression of CRC by positively regulating PRUNE2 transcription.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, we previously demonstrated that PRUNE2 has the same functions as FOXF2 in CRC, and the survival prognosis of patients with low expression of PRUNE2 was poor. 42 Thus, we speculated that FOXF2 may regulate PRUNE2 and that this regulatory correlation may play an important role in CRC. Herein, we identified PRUNE2 as a novel transcriptional target of FOXF2 and demonstrated that FOXF2 regulated the proliferation and progression of CRC by positively regulating PRUNE2 transcription.…”
Section: Discussionmentioning
confidence: 99%
“… 36 A previous study demonstrated that PRUNE2 decreased cell survival, proliferation, invasion, and tumorigenicity and promoted apoptosis, suggesting that PRUNE2 functions as a tumor-suppressive gene in CRC. 42 However, the role of PRUNE2 and its mechanism in CRC are still unclear. Taking the above into consideration, we assumed that PRUEN2 mediates the inhibitory function of FOXF2 in the development and pathogenesis of CRC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation